More on KG Sombor Index of Graphs - Mitesh J. Patel; Kajal S. Baldaniya; Ashika Panicker (International Journal of Mathematics And its Applications, 2025)
Let G=(V(G),E(G)) be a graph of order n and size m. The KG Sombor index of graph G is defined as KG(G) = _ued^2_u+d^2_e, where _ue indicates summation over vertices u V(G) and the edges e V(G) that are incident to u. In this paper, we found some useful correlation between KG Sombor index and dielectric constant as well as density of various organic hydrocarbons. We also derive some new bounds of KG Sombor index of graph with respect to different topological indices using mathematical inequities. Moreover we obtain KG Sombor index of corona product of two graphs.